The Role of Parenting in Cultivating Environmental Attitudes in Early Childhood in Digital Era - Afwanni, Tiwi; Alim, Rahmawati Nur; Cholimah, Nur (Program Studi Magister Pendidikan Anak Usia Dini, 2024)
In this digital era, parenting plays an important role in shaping environmental awareness and nature-friendly behavior in early childhood. Children at this time are often exposed to technology from an early age, so excessive use can affect children's attitudes and behavior towards the environment. This study aims to identify the role of appropriate parenting on environmental care in the digital era in early childhood. This research uses a qualitative study with a literature review research method by collecting various scientific sources. This research aims to convey information about how the role of parenting can affect children's environmental care attitudes in the digital era. An important finding in this study is that the role of parents in shaping children's character, especially in the digital era, is very important. Parents must understand the characteristics of children in the digital era, apply appropriate parenting patterns and build effective communication with children. The importance of applying democratic and authoritative parenting, in helping children develop positive environmental awareness. Therefore, the importance of early religious and moral values education as an effort to instill environmental awareness in children. Parents' involvement in children's learning, both at home and at school, is a key factor in shaping environmental awareness in early childhood.